Learning Motivation and Students' Critical Thinking Ability in Science Learning through a Problem Based Learning Model Assisted by Video Media - Pertiwi, Anisa Yuni; Sri Mulyani Endang Susilowati, Sri Mulyani Endang Susilowati; Khumaedi, Khumaedi (Journal of Primary Education)
This study purpose of determining the effectiveness of PBL learning models assisted by video media on learning motivation and students 'critical thinking ability, determine the correlation between learning motivation and students' critical thinking ability. This research is an experimental research with quasi-experimental design in the form of one-group pre-test – post-test. The research subjects were 63 students of fifth grade in Public Elementary School Danareja 02 and Public Elementary School Cilongok 02 Balapulang, Tegal in the 2018/2019 academic year. Data collected by questionnaire, test, interview, documentation, and observation. Learning motivation scores are obtained by learning motivation questionnaires and critical thinking ability by test. Data of motivation and critical thinking are analyzed quantitatively by completeness test, N-Gain test, and correlation test between learning motivation and critical thinking ability. The results showed that science learning through PBL learning models assisted by video media effective to increase learning motivation and critical thinking ability on experimental class students. The result of the learning motivation N-Gain test is 0.56 medium criteria and result of the critical thinking ability N-Gain test is 0.54 medium criteria; there is a correlation between students' motivation and critical thinking ability. Learning motivation affects critical thinking ability by 34.9%, while the remaining 65.1% caused by other factors.